Students' perceptions, teachers' implementation and evaluation of science performance tasks in the chemistry classrooms : a case study - CAPARAS, ANN JOAN HOPE (Archīum Ateneo, 2018)
This study used the case study method to determine students perceptions of performance tasks. It also aimed to assess teacher-designed Performance Tasks in Chemistry so to determine the challenges that teachers face in the design, implementation and evaluation of the performance tasks and to establish a system of support that the school can provide for the teachers in the design, implementation and evaluation of performance tasks. Using the Student Perceptions Assessment Questionnaire, it is found out that majority of the students agree that the teacher-designed Performance Tasks in Chemistry in terms of Congruency with Planned Learning, Authenticity, Student Consultation, Transparency and Diversity. Using the Performance Task Assessment Tool and semi-structure interview majority of the teachers felt that the all the Performance Tasks addressed standards alignment and student learning. It is recommended that teachers be trained in the design, implementation and evaluation of Performance Tasks as well as the design of rubrics to maximize assessment.